1999
DOI: 10.1074/jbc.274.21.14786
|View full text |Cite
|
Sign up to set email alerts
|

Myocyte-dependent Regulation of Endothelial Cell Syndecan-4 Expression

Abstract: Syndecan-4 is a unique member of the syndecan gene family that has the ability to bind and activate protein kinase C-␣. Whereas increased syndecan-4 levels have been noted in ischemic hearts, little is known regarding the regulation of its expression. To investigate the role of cardiac myocytes in induction of syndecan-4 expression, human endothelial cells (ECV304) were exposed to a medium conditioned by primary mouse cardiac myocytes or H9c2 cells. The medium conditioned by hypoxic but not normal myocytes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 20 publications
1
48
0
Order By: Relevance
“…Collectively, it is therefore conceivable that TNF-␣ is the predominant cytokine driving the synergy and that it acts mainly at the posttranscriptional level. This role of TNF-␣ has been described for a number of other genes, including bradykinin receptor (34), syndecan-4 (35), and Fc␥RIIb (36).Two AUUUA sequence motifs are located in the 3Ј-untranslated region of the eotaxin-1 mRNA. These sequences have been implicated in the stabilization of mRNA (37).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, it is therefore conceivable that TNF-␣ is the predominant cytokine driving the synergy and that it acts mainly at the posttranscriptional level. This role of TNF-␣ has been described for a number of other genes, including bradykinin receptor (34), syndecan-4 (35), and Fc␥RIIb (36).Two AUUUA sequence motifs are located in the 3Ј-untranslated region of the eotaxin-1 mRNA. These sequences have been implicated in the stabilization of mRNA (37).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Mac-1-positive cells expressing syndecan-4 strongly were considered to be monocytes and Kupffer cells in the sinusoids of the liver. Zhang et al (25) have found that TNF-␣ induces syndecan-4 expression in endothelial cells by both increasing syndecan-4 gene expression in an NF-B-dependent manner and by extending the half-life of syndecan-4 mRNA. TNF-␣ concentration in plasma was elevated 1 h after LPS injection, which was prior to syndecan-4 induction.…”
Section: Discussionmentioning
confidence: 99%
“…DNA synthesis was measured by performing a BrdU incorporation assay with a commercially available kit (Roche) as directed by the manufacturer. Cardiomyocyte-conditioned medium was collected as previously described (43). Briefly, cultured cardiomyocytes were starved in DMEM without FBS and were pretreated with EPO (10 U/ml) or saline for 48 hours, and then the medium was collected and transferred to HUVECs.…”
mentioning
confidence: 99%